Jugements étudiants sur l'intérêt des études : quelques enseignements tirés d'une comparaison internationale - Alain Fernex; Laurent Lima (Les éditions de la Maison des sciences de l'Homme, 2006)
The economic and sociological literature has been interested for a few decades in the transformations of higher education. An international research undertaken within the FREREF's framework offers data relating to the judgements students express about their studies (working conditions, difficulties, expectations). In this article, the authors discuss and relate three dimensions of the issue : What benefits do the students hope to draw from their studies ? What typology can be establish on these bases ? What are, in the students' eyes, the main characteristics of their studies ? What requirements are they submitted to ? What judgements do they express on their progression ? The article highlights a great diversity of expressed expectations (according to the domain of studies, the country) and establishes the existence of relations between the judgements related to the interest of the studies and those related to progression.